Hydroclimate variability during the last 2700 years based on stalagmite multi-proxy records in the central-western Mediterranean. (1st October 2021) - Cisneros, Mercè; Cacho, Isabel; Moreno, Ana; Stoll, Heather; Torner, Judit; Català, Albert; Edwards, R. Lawrence; Cheng, Hai; Fornós, Joan J.
Abstract: This study presents the first high-resolution speleothem-based hydrological reconstruction for much of the last 2.7 kyr in the central-western Mediterranean. The paleohydrological information comes from a combination of five U-Th dated stalagmites from two Mallorca island caves. Interpretations are based on high-resolution records of δ 18 O, δ 13 C and trace element analyses combined with information from mineralogical X-ray diffraction, fabrics and morphological features, and cave monitoring data. None of the studied stalagmites cover the whole 2.7 kyr period but they provide sufficient overlap to replicate most of the discussed climatic intervals with the exception of the Medieval Climate Anomaly (MCA), which is represented by a hiatus. Taking into account the results of five years farmed calcite collected in glass plates and cave environmental parameters, we argue that main patterns in the stalagmite geochemical records are mostly controlled by changing rates of prior calcite precipitation (PCP) that respond to hydrological changes in the region. We apply a principal component analysis to the stalagmite geochemical data set and a composite δ 18 O record to obtain a robust regional hydrological record. This record supports wet conditions for the early Roman Period (RP), the first half of the Early Middle Ages (EMA) and the Little Ice Age (LIA), and drier conditions for the late RP, the late EMA and the entire MCA. These results are discussed in the context of other climatic and oceanographic records from the region including paleo North Atlantic Oscillation (NAO) records. This ocean-atmosphere approach suggests complex non-stationary climate patterns for the last 2.7 kyr, including the occurrence of both wet-warm and wet-cold intervals and underlying the complex interaction of factors controlling climate evolution in the region. Overall, positive (negative) NAO phases appear coincident with drier (wetter) conditions for all the examined period at decadal time-scales. Highlights: The first speleothem-based hydrological reconstruction for the last 2.7kyr for the central western Mediterranean. Sub-decadal hydroclimate variability is inferred from δ 18 O composite record derived from five stalagmites. Wet (dry) conditions characterize the early (late) RP, the first (second) half of the EMA and the LIA (the MCA). Terrestrial and marine data is combined to reconstruct climate of the last 2.7kyr in the central-western Mediterranean.